Editorial - Apivatthakakul, MD, Theerachai (Journal of Southeast Asian Orthopaedics, 2022)
The year 2018 is passing very quickly. The JRCOST is about to launch Volume 42, number 1-2 for January-April, 2018. In the change of Orthopaedic training curriculum according to WFME, we hope residents should have their publications more often and being compulsory for every trainee. Apart from residents, we are also trained many fellows in various subspecialties. They should begin with JRCOST and progress to high impact journal for the next step. Nowadays, the medical students are also trying harder to extend their portfolios with publications, and get the well support from all medical schools. We hope the brighter future with our young generation. In this issue, we have 2 research articles which are “Patterns and Differences of Acetabular Dome Wear of Normal and Operated Hip Joints between the Unipolar and Bipolar Prostheses in the Femoral Neck Fracture Surgery” and “The incidence of Anxiety and Depression in Patients with Spinal Injury at Siriraj Spinal Unit”. We also published 2 case reports. They are “A Case Report of Posterior Shoulder Dislocation with Greater Tuberosity Fracture” and “Anterior Extrusion of Bone Graft after Posterior Lumbar Interbody Fusion with development Deep Vein Thrombosis: Case Report and Literature review”. All of our articles are welcome for comment. Please write a letter to editor. Hope to hear from you.